Stress‐induced C14→C15 phase transformation in a Zr(Fe, Cr)2 Laves structured nanophase. Issue 1 (28th November 2019) - Yuan, Fusen; Liu, Chengze; Han, Fuzhou; Zhang, Yingdong; Muhammad, Ali; Guo, Wenbin; Gu, Hengfei; Li, Geping
Abstract : The stress‐induced C14→C15 phase transformation in an individual nanophase was explored by means of the transmission electron microscopy technique. Abstract : The C14 (hexagonal close‐packed) and C15 (face‐centred cubic) close‐packed structures are found to coexist in an individual Zr(Fe, Cr)2 Laves structured nanophase in Zircaloy‐4 alloy with shear deformation. The orientation relationship between C15 and C14 is [ 10]C15 //[11 0]C14 and ( 11)C15 //(0001)C14 . The stacking faults (SFs) in the C15 structure and the high‐density SFs between C15 and C14 have been identified using transmission electron microscopy, which showed they originated on close‐packed planes by emission of 1/6⟨ ⟩ Shockley partial dislocations from the phase boundary. Furthermore, the stress‐induced C14→C15 phase transformation took place during the shear deformation.